Superantigenicity analysis of staphylococcal enterotoxins SElK and SElQ in a mouse model. Issue 38 (30th April 2015) - Kang, Hongzhi; Deng, Hui; Shen, Menglu; He, Xianzhi; Xia, Yihe; Li, Yi; Liang, Zhixuan; Wang, Hongjun; Huang, Jinhai
<x xml:space="preserve">Abstract</x> Staphylococcal enterotoxins (SEs) are superantigenic toxins secreted by Staphylococcus aureus that is involved in causing food poisoning and human diseases.